Global Identification of the Full-Length Transcripts and Alternative Splicing Related to Phenolic Acid Biosynthetic Genes in Salvia miltiorrhiza - Xu, Zhichao; Luo, Hongmei; Ji, Aijia; Zhang, Xin; Song, Jingyuan; Chen, Shilin (Frontiers in Plant Science, 2016)
Salvianolic acids are among the main bioactive components in Salvia miltiorrhiza, and their biosynthesis has attracted widespread interest. However, previous studies on the biosynthesis of phenolic acids using next-generation sequencing platforms are limited with regard to the assembly of full-length transcripts. Based on hybrid-seq (next-generation and single molecular real-time sequencing) of the S. miltiorrhiza root transcriptome, we experimentally identified 15 full-length transcripts and 4 alternative splicing events of enzyme-coding genes involved in the biosynthesis of rosmarinic acid. Moreover, we herein demonstrate that lithospermic acid B accumulates in the phloem and xylem of roots, in agreement with the expression patterns of the identified key genes related to rosmarinic acid biosynthesis. According to co-expression patterns, we predicted that 6 candidate cytochrome P450s and 5 candidate laccases participate in the salvianolic acid pathway. Our results provide a valuable resource for further investigation into the synthetic biology of phenolic acids in S. miltiorrhiza.